2013
DOI: 10.1136/bmj.f6070
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of telemonitoring integrated into existing clinical services on hospital admission for exacerbation of chronic obstructive pulmonary disease: researcher blind, multicentre, randomised controlled trial

Abstract: Objective To test the effectiveness of telemonitoring integrated into existing clinical services such that intervention and control groups have access to the same clinical care.Design Researcher blind, multicentre, randomised controlled trial.Setting UK primary care (Lothian, Scotland).Participants Adults with at least one admission for chronic obstructive pulmonary disease (COPD) in the year before randomisation. We excluded people who had other significant lung disease, who were unable to provide informed co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
318
2
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(350 citation statements)
references
References 33 publications
24
318
2
6
Order By: Relevance
“…Two randomized trials of telemonitoring in CHF patients [21] and COPD [34] patients did not show a reduction in rehospitalizations. A recent Cochrane review of telemonitoring in heart failure that included studies where participants were recruited from the hospital showed no consistent benefit relative to hospitalization or mortality but improved quality of life [35].…”
Section: Discussionmentioning
confidence: 89%
“…Two randomized trials of telemonitoring in CHF patients [21] and COPD [34] patients did not show a reduction in rehospitalizations. A recent Cochrane review of telemonitoring in heart failure that included studies where participants were recruited from the hospital showed no consistent benefit relative to hospitalization or mortality but improved quality of life [35].…”
Section: Discussionmentioning
confidence: 89%
“…The study concluded that among patients ''with a history of admission for exacerbations of COPD, telemonitoring was not effective in postponing admissions and did not improve patients' quality of life.'' 125 The investigators speculated that the positive effects of telemonitoring reported in earlier studies may have been due to enhancements of clinical service in the telemonitoring group.…”
Section: Telemedicine and E-health September 2014mentioning
confidence: 99%
“…125 The intervention consisted of daily patient responses entered on a touchscreen device to questions about symptoms and use of treatment and oxygen saturation. The study was focused on investigating the effects of telemonitoring technology.…”
Section: Telemedicine and E-health September 2014mentioning
confidence: 99%
“…Obviously, the digitalization of our society will result in changes in future communication forms. Introduction of telemonitoring itself does not necessarily improve QOL or reduce the number of hospitalizations [6567]. If introduced, it is important to adjust the tele-intervention to fit the patient’s needs and technical skills [66].…”
Section: Telemedicinementioning
confidence: 99%